CREATING MAPS OF AGRICULTURAL CROPS USING MODERN GIS PROGRAMS - Azimjon Axmadov (TADQIQOTLAR.UZ, 2024)
Annotation: In this article, we explore new approaches to calculating and improving the efficiency of Geographic Information System (GIS) applications and resource management. It aims to identify solutions for addressing challenges related to GIS utilization, finding their solutions through GIS tools, and defining the existing opportunities and prospects in this field. The article specifically discusses creating electronic maps for rural areas.